Can the performance of semi-inverted hydrocyclones be similar to fine screening?. (15th January 2020) - Jokovic, Vladimir; Morrison, Robert; Alexander, Daniel
Graphical abstract: Highlights: Water split to Underflow in case of the Semi-inverted hydrocyclone is reduced compared with the vertical hydrocyclone. The cut size for a semi-inverted cyclone is higher than for conventional hydrocyclone. Semi-inverted hydrocyclone reduces the misclassification of fines. These results are comparable to reported results for fine wet screening. Abstract: The devices most commonly used for classification in the mining industry are hydrocyclones. Hydrocyclones have been preferred over most other devices due to low operating cost and a small footprint and have not received as much attention as more expensive comminution units, and their technological progress has been incremental. A classification study using semi-inverted hydrocyclones was conducted to determine if a hydrocyclone could be operated in a way that would produce similar results to a screen. The results from the study were encouraging with substantial reduction in water split to coarse product ( R f ) and much coarser cut sizes. A hydrocyclone with lower water split to underflow ( R f ) will improve classification of fines which would otherwise be sent back to the grinding circuit. The ability of hydrocyclones to cut coarser would potentially expand their application in the areas where the fine screens are currently in use. Therefore, the very low R f and coarser cut are of paramount importance for a step change in future industrial operation. Other potential benefit compared with fine screens are reduction of the footprint required for the installation and in challenges in even slurry distribution. The classification performance of a semi-inverted hydrocyclone will be presented in this paper.